Serum cystatin c concentrations in patients with graves' ophthalmopathy - Can, Nagehan; Ozsoy, Ercan; Kobat, Sabiha Gungor; Yusufoglu, Elif; Ilhan, Nevin; Demir, Tamer (Korean Ophthalmological Society (KOS), 2020)
Purpose: To evaluate the concentration of serum cystatin C (CysC) in patients with Graves' ophthalmopathy (GO) and the usability of the serum CysC concentrations in the follow-up of the disease. Methods: Thirty patients with GO and 30 healthy age-matched volunteers were included in this cross-sectional study. GO was diagnosed based on the European Group on Graves' Orbitopathy consensus. Serum thyroid-stimulating hormone, free triiodothyronine, free thyroxine, and CysC concentrations were measured in the participants. The serum CysC concentrations were compared between patients with GO and controls. Patients with GO were subdivided into hyperthyroid and euthyroid patients, and their serum CysC concentrations were compared. In addition, the CysC concentrations in hyperthyroid and euthyroid patients with GO were compared separately with those of healthy subjects. Kruskal-Wallis test and Student's t-test were used for statistical evaluation. Results: The mean serum CysC concentrations in GO patients and controls were 1.04 ± 0.36 and 0.74 ± 0.09 mg/L, respectively. There was a statistically significant difference in the serum CysC concentrations between patients with GO and control subjects (p < 0.001). Fifteen patients had hyperthyroid status, and 15 patients had euthyroid status. The mean serum CysC concentrations in hyperthyroid and euthyroid patients with GO were 1.35 ± 0.22 and 0.72 ± 0.13 mg/L, respectively. Serum CysC concentrations were significantly higher in hyperthyroid patients than in euthyroid patients (p = 0.001). In addition, hyperthyroid patients had significantly higher serum CysC concentrations than healthy subjects. Among patients with GO, 21 and nine had mild and moderate- to-severe GO, respectively. Active and inactive GO were observed in eight and 22 patients, respectively. Conclusions: The serum CysC concentrations in hyperthyroid patients were higher than those in healthy subjects. Moreover, hyperthyroid patients had higher serum CysC concentrations than euthyroid patients. Further studies with a larger sample size are needed to confirm these results. © 2020 The Korean Ophthalmological Society.
Keywords: Cystatin C; Exophthalmos; Serum; Thyroxine; Triiodothyronine